Reframing NCDs? An analysis of current debates. Issue 1 (1st January 2019) - Adjaye-Gbewonyo, Kafui; Vaughan, Megan
ABSTRACT: There have been many debates in recent years as to whether the communicable disease versus non-communicable disease (NCD) division is a meaningful one in disease classification. Several critiques have been raised about the framing of NCDs, regarding not only the prominent role that infections play in the aetiology of NCDs, but also the communicability of many social determinants of NCDs and the individualistic, 'lifestyle' framing of NCDs that tends to focus on health behaviours to the neglect of socio-political, environmental, and structural determinants of health. In this paper, we give a historical overview of the usage of the NCD terminology and analyse some of the recent debates regarding the naming and framing of NCDs. We argue that a lack of reflection on the assumptions underlying the naming and framing of NCDs may lead to the collection of insufficient epidemiological data, the development of inappropriate interventions and the provision of inadequate care. Work in social epidemiology, health promotion, medical anthropology, demography, and other fields may provide insights into the ways in which efforts targeting NCDs may be reframed to improve impact and efficacy. In addition, concepts such as multimorbidity and syndemics, frameworks such as ecosocial theory and approaches based in the social sciences may provide a way forward in the conceptualization of disease.